Gomisin A Attenuates Cerebral Ischemia/Reperfusion Injury Through Activation of the VEGF/PI3K/AKT/NOS3 Signaling Pathway - Chenghe Zhao; Jiayue Yu; Kexin Liu; Shuangling Wang; Wenping Jing; Ziyi Zhao; Wenyue Zhuang (Cell Biochemistry and Biophysics, 2026)

Microbial functional strategy divergence mediates SOC mineralization in an eroded agricultural landscape - Rui Qian; Lei Gao; Yanling Wang; Evgenios Agathokleous; Junliang Zou; Xinhua Peng (Applied Soil Ecology, 2026)

Glycolipid metabolism reprogramming and transcriptional splicing of ARID4B genes during the response to summer seawater warming in Patinopecten yessoensis - Hongbo Lu; Mingyue Zhang; Chuanyan Yang; Dongli Jiang; Xin Kang; Qiuyu Zhang; Lingling Wang; Linsheng Song (Marine Pollution Bulletin, 2026)

Sedimentary DOM composition governs the environmental mobility of palladium in tropical island estuaries - Zhixin Li; Yuyan Liu; Ling Wang; Hongwei Yi; Rui Xu; Jianan Liu; Haofeng Liu; Ye Li; Min Liu (Marine Pollution Bulletin, 2026)

The regulation of CgmiR-29 in glycogenolysis in the Pacific oyster under high-temperature stress - Hairu Xu; Lei Gao; Xingyi Feng; Jiayu Ye; Honglu Liu; Mingyan Bao; Lingling Wang; Linsheng Song (Aquaculture, 2026)

Research on the mechanism of Eucalyptus tannins inhibiting soil respiration - Xinya Li; Miaoling Wang; Gairen Yang; Zhifeng Xie; Shiqi Wei; Lisha Li; Yusong Deng; Huili Wang (Applied Soil Ecology, 2026)

Source tracking of antibiotic resistance genes emitted via livestock aerosols: A case study of a pig farm - Chu Peng; Xinling Wang; Mengxi Li; Ting Cai; Junjie Zhang; Jiao Wang; Chunguang Liu; Lei Wang; Hongwen Sun (Applied Soil Ecology, 2026)

Phosphorus-laden biochar modulates soil microbial communities and promotes phosphorus cycling in acidic soils - Zeinab El-Desouki; Yehia Abouseif; Jiyuan Wang; Muhammad Qasim; Saba Babar; Xiaoyang Xia; Xiangling Wang; Cuncang Jiang (Applied Soil Ecology, 2026)

Synergy and antagonism: Differential responses of soil environmental factors under antibiotic pollution - Ling Wang; Kunlong Hui; Dong Wang; Jie Sun; Ying Yuan; Wenbing Tan (Applied Soil Ecology, 2026)

Continuous biochar application ameliorates saline-alkali soils: Effects on soil multifunctionality, salt redistribution, microbial dynamics, and cotton productivity over two years - Xiangling Wang; Xiaoyang Xia; Muhammad Riaz; Jiyuan Wang; Cuncang Jiang (Applied Soil Ecology, 2026)

Syringa oblata maintains rhizosphere r-strategists and microbial functions by regulating exudates in root tip zone under drought - Huiling Wang; Jiarui Chen; Hang Jing; Benshuai Yan; Furong Wei; Sha Xue; Guoliang Wang (Applied Soil Ecology, 2025)

Responses of complete and incomplete ammonia oxidizers to farmland reversion to forest in Ferralsols - Pengfei Zhang; Yongpeng Zhao; Lihua Ma; Shuling Wang; Min Yang; Alan L. Wright; Xianjun Jiang (Applied Soil Ecology, 2025)

Belowground herbivory alter invasive plant-soil feedback and reduce aboveground herbivory - Lei Wang; Ailing Wang; Jie Sun; Zhanhui Tang (Applied Soil Ecology, 2025)

Addition of bacterial-feeding nematodes contributes to soil phosphorus availability by affecting the mineralization of moderately labile organic phosphorus - Jigao Wang; Kai Wei; Jialiang Tang; Chaoyan Yuan; Yanling Wang; Xiaoming Sun; Bo Zhu (Applied Soil Ecology, 2025)

The Immune Priming in Aquaculture Invertebrates: Inspiration From Cellular Perspective and Future Investigation - Weilin Wang; Lingling Wang; Linsheng Song (Reviews in Aquaculture, 2025)
Aquatic invertebrates account for more than 33.4% of global aquaculture production and are important aquaculture animals worldwide. Although the frequent outbreaks of diseases and the lack of disease prevention strategies have greatly hindered further development of the invertebrate aquaculture industry. Immune priming is a phenomenon that invertebrates mount a faster and stronger secondary response than that of the primary response when encountered with a given microbe. It has been demonstrated to be present in a wide range of aquaculture species and would provide a fresh idea for disease prevention. As the main executors of immune defense in invertebrates, the circulating hemocytes are short‐lived, and the solution for the paradox of keeping a long‐lasting immune protection might lie in the formation of long‐lived memory cells in immune priming. As a reference for the access of memory cell formation processes in aquaculture invertebrates, the cellular kinetics including expansion, contraction, and memory formation of lymphocytes in the adaptive immunity of vertebrates are discussed. Then the features of hemocytes in aquaculture invertebrates, and their kinetic changes of cell number and immune capacity during immune priming are summarized for the knowledge of a stronger secondary immune response. The regulatory roles of epigenetic modification and metabolic reprogramming in immune priming and their possible functions in memory cell formation and identification are proposed to be preferentially investigated for further clarifying the mechanism of immune priming, which might provide a novel entrance for understanding the mechanisms of immune priming and developing disease prevention strategy in aquaculture invertebrates.

Stability of nitrogen-cycling microbial communities and impact on microbial nitrogen function under different land use practices - Yongpeng Zhao; Zhihui Wang; Kai Cai; Shuling Wang; Alan L. Wright; Xianjun Jiang (Applied Soil Ecology, 2024)

Microbial composition in saline and alkaline soils regulates plant growth with P-solubilizing bacteria - Xiaodan Sun; Wei Wang; Shijie Yi; Fengrong Zheng; Zhaohui Zhang; Sulaiman Almwarai Alharbi; Ekaterina Filimonenko; Zongling Wang; Yakov Kuzyakov (Applied Soil Ecology, 2024)

Seasonal prediction of crop yields in Ethiopia using an analog approach - Meijian Yang; Guiling Wang; Shu Wu; Paul Block; Rehenuma Lazin; Sarah Alexander; Jonathan Lala; Muhammad Rezaul Haider; Zoi Dokou; Ezana Amdework Atsbeha; Marika Koukoula; Xinyi Shen; et al. (Agricultural and Forest Meteorology, 2023)

Divergent tree radial growth patterns of Qinghai spruce (Picea crassifolia) at the alpine timberline along a moisture gradient in the Qilian mountains, Northwest China - Weiguo Zhang; Xiaohua Gou; Wenhuo Liu; Jinbao Li; Jiajia Su; Naveen Dilawar; Fangjingcheng Zhu; Jingqing Xia; Miaomiao Du; Lingling Wang; Qipeng Sun; Yiran Zhang; et al. (Agricultural and Forest Meteorology, 2023)